IMPLEMENTASI MANAJEMEN PERENCANAAN DALAM MENINGKATKAN SIKAP PROSOSIAL DI SEKOLAH MENENGAH PERTAMA ILMU TEKNOLOGI DARUL FALAH PACET - Adi Rosadi; Muchammad Erihadiana; Muhibinsyah Muhibinsyah (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
An interesting phenomenon that exists in SMP IT is the problem of the character of students who are currently experiencing degradation or decline, decreased appreciation of human values, such as lack of respect for parents, teachers, and even fellow friends, study time is replaced by social media activities, students are more engrossed in talking on social media and often ignore the real world. This then becomes the basis for researchers to be interested and researching this theme. This study uses a descriptive qualitative research approach with a type of field research. collection used are interview, observation and documentation analysis. The data analysis technique is by using data reduction and triangulation. The results showed that the forms of planning management implementation were SWOT analysis, conducting discussions, determining the character to be developed, determining activities and forming a development team. The process of implementing planning management is checking its implementation both inside and outside the classroom using discussion methods, habituation, and examples that are familiar to school members. The impact or implication of the process of implementing planning management in improving social attitudes in the Darul Falah Pacet Middle School of Technology is increasing self-awareness in being social with students, teachers and education staff in various educational institutions at all levels so as to give birth to an educational profile with character.